2021
DOI: 10.3389/fphy.2021.654918
|View full text |Cite
|
Sign up to set email alerts
|

A Flexible Microdevice for Mechanical Cell Stimulation and Compression in Microfluidic Settings

Abstract: Evidence continues to emerge that cancer is a disease not only of genetic mutations, but also of altered mechanobiological profiles of the cells and microenvironment. This mutation-independent element might be a key factor in promoting development and spread of cancer. Biomechanical forces regulate tumor microenvironment by solid stress, matrix mechanics, interstitial pressure, and flow. Compressive stress by tumor growth and stromal tissue alters cell deformation and recapitulates the biophysical properties o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(49 citation statements)
references
References 47 publications
2
47
0
Order By: Relevance
“…To extend on what is possible with existing systems and increase robustness of cyclic cell compression results, control of the pressure application was optimized by evaluating the effect of device fabrication variations. To recall dimensions of the micro-piston device we developed in [5], the height of the cell culture channel was on average 313 µm, while micro-pistons were measured as around 206 µm in PDMS replicas. Once assembled, the gap these layers created between the bottom of the micro-piston and the glass surface was measured as on average 108 µm.…”
Section: Comparison Of the Experimental And Computational Results In ...mentioning
confidence: 99%
See 3 more Smart Citations
“…To extend on what is possible with existing systems and increase robustness of cyclic cell compression results, control of the pressure application was optimized by evaluating the effect of device fabrication variations. To recall dimensions of the micro-piston device we developed in [5], the height of the cell culture channel was on average 313 µm, while micro-pistons were measured as around 206 µm in PDMS replicas. Once assembled, the gap these layers created between the bottom of the micro-piston and the glass surface was measured as on average 108 µm.…”
Section: Comparison Of the Experimental And Computational Results In ...mentioning
confidence: 99%
“…A previously developed finite element model (FEM) based on hyperelastic Saint Venant-Kirchhoff theory for actuation of the flexible microdevice [5] SKOV-3 cells at a seeding density of 1.5 × 10 6 cells/ml were loaded using piston-retracted loading. In this method of chip loading with cells, the PDMS membrane with the attached micro-piston was retracted out of the culture channel towards the top control channel using an applied negative pressure of 615 (-615) mbar to favour flow of seeding solution for homogenous distribution of cells.…”
Section: Computational Model and Experimental Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…Several strategies have been developed to add biomechanical cues into microfluidic devices, such as the application of shear stresses or compression forces, to better study cancer progression and chemoresistance. For example, Onal et al created a microfluidic device integrated with actuators to apply compression on SKOV-3 cells [ 172 ]. It has been reported that cells under compression stimulation displayed invasive morphology, increased proliferation and chemoresistance [ 173 ].…”
Section: 3d Ovarian Cancer Modelsmentioning
confidence: 99%